Circular RNA lysophosphatidic acid receptor 3 (circ-LPAR3) enhances the cisplatin resistance of ovarian cancer. Issue 2 (1st February 2022) - Liu, Xuemei; Yin, Zhiping; Wu, Yanjun; Zhan, Qian; Huang, Honghong; Fan, Jiangtao
ABSTRACT: Circular RNA (circRNA) is considered to be an important regulator that mediates cancer chemoresistance. But whether circ-LPAR3 is involved in ovarian cancer (OC) cisplatin (DDP) resistance is unclear. The circ-LPAR3, miR-634 and pyruvate dehydrogenase kinase 1 (PDK1) expression was measured by quantitative real-time PCR (qRT-PCR). Cell cisplatin resistance and viability were measured by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl-tetrazolium bromide (MTT) assay. In addition, cell colony number, apoptosis, and metastasis were assessed by colony formation assay, flow cytometry and transwell assay. Furthermore, in vivo experiments were performed by constructing mice xenograft models. RNA interaction was confirmed by dual-luciferase reporter assay, and PDK1 protein expression was examined by Western blot analysis. Our results showed that circ-LPAR3 was markedly upregulated in DDP-resistant OC tissues and cells. Silencing of circ-LPAR3 enhanced the DDP sensitivity of OC cells and tumors. MiR-634 could interact with circ-LPAR3, and its inhibitor overturned the regulation of si-circ-LPAR3 on cell DDP resistance. Additionally, PDK1 was targeted by miR-634, and its overexpression inverted the effect of miR-634 on cell DDP resistance. To sum up, circ-LPAR3 might contribute to the DDP resistance of OC via the miR-634/PDK1 axis. Graphical abstract: uf0001